Highly corrosion-resistant Ni-Cr-Mo steel with excellent weldability and surface properties and method for producing the same
By adjusting the chemical composition of Ni-Cr-Mo steel, satisfying specific element proportions and relationships, weldability and surface properties are optimized, and the problems of cracks, surface defects and uneven gloss during welding and thermal processing are solved.
Patent Information
- Application Number
- CN202010630768.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-08-22
- Filing Date
- 2020-07-03
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2040-07-03
AI Technical Summary
In the prior art, Ni-Cr-Mo steel has problems of cracks, surface defects and uneven gloss during welding and thermal processing, and the optimization of welding properties and surface properties has not been fully considered.
By adjusting the chemical composition of Ni-Cr-Mo steel, ensure that it contains specific element ratios, such as C, Si, Mn, P, S, Ni, Cr, Mo, W, Cu, N, B, Ca, REM, Al , Ti and O satisfy specific relationships to optimize weldability and surface properties.
Excellent weldability to prevent weld cracks is achieved, and excellent surface properties are obtained by improving thermal workability, and the problems of uneven gloss and surface defects are solved.
Smart Images

Figure CN112410656B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a Ni-Cr-Mo steel which is used for a flue gas desulfurization device of a thermal power plant, a ship scrubber, etc. and has excellent corrosion resistance and excellent weldability and surface properties. Background Art
[0002] High-Ni steel containing a large amount of Cr and Mo is used in devices operating in severe corrosive environments due to its excellent corrosion resistance, but this alloy is often assembled by welding, and excellent weldability is also required. If the device is large-scale or the design is complex, cracks in the welded metal often become a problem, and solutions need to be sought from the base material.
[0003] In addition, since the hot workability of high-Ni steel is poor, problems related to surface properties such as surface defects and cracks often occur. Although improvements have been made, the current usage environment is becoming increasingly severe. For example, if a large amount of Cr, Mo, and N are added to high-Ni steel to improve corrosion resistance, the current solution is insufficient, and problems caused by hot working occur, and no solution has been found.
[0004] There are many issues related to hot working, including strip defects and cracks at the ends of plates and strips. In addition, uneven gloss on the plane of the plates and strips is also considered a problem, and all require solutions.
[0005] There are many improvements related to hot workability. For example, in Patent Document 1, REM (Rare Earth Metal) is added to a Ni-Cr-Mo alloy containing Cu to achieve an improvement in the reduction of area at 900°C. However, in this technology, no research related to weldability has been conducted. In addition, REM is an element that is easily oxidized. In this technology, there is a concern about quality deterioration due to the formation of oxides on the weld bead.
[0006] In addition to this technology, Patent Document 2 proposes an alloy that suppresses the decrease in overheat temperature by controlling the contents of C, Cr, Mo, Al, Ti, and Fe using a relational expression, and further improves the alloy by the fixation of S due to the addition of Ca. In plates and strips, this is proposed as a solution to cracks at the ends called so-called edge cracks, but weldability is not considered in this technology either.
[0007] Patent Document 3 proposes a steel which is an example of austenitic stainless steel but is improved by adding one or more of Ca, REM, and B. Since this technology targets alloys with a low Mo content, it is believed that there are differences in the degree of poor hot workability as a matrix, and it is unclear whether it can be applied to Ni-Cr-Mo alloys. In addition, weldability has not been studied, and it is unclear whether it has sufficient characteristics when considering the manufacture of the device.
[0008] Although both are examples of stainless steel, Patent Document 4 proposes adding B and controlling the values of the relationship formula including the contents of Cu, Mo, and O to a certain range, thereby producing a steel having excellent hot workability. The steel used as the subject has a small amount of Mo and Ni. Therefore, it is believed that there is a difference in the degree of poor hot workability as a matrix, and it is unclear whether it can be applied to Ni-Cr-Mo steel. In addition, similar to the above, weldability has not been studied, and the manufacturability of the device is questionable.
[0009] Similarly, in Patent Document 5, an austenitic stainless steel showing excellent corrosion resistance is proposed, wherein, although it is recorded that hot workability is improved by adding B and Ca, there are no examples and the details are unknown. There is also no research on weldability, but the focus is on improving brazing properties, with the purpose of applying to automotive equipment such as EGR (exhaust gas recirculation). Therefore, the characteristics of the welded portion are unclear.
[0010] As mentioned above, the conventional technology only focuses on hot workability, and there is no research on the uneven surface gloss produced in high-Mo steel such as Ni-Cr-Mo steel. As a result, it is impossible to obtain plates and strips with excellent surface properties. Uneven gloss is a defect in appearance and is not beautiful, but it is not only beautiful. The contents of chemical devices and corrosion products adhere to this part, which causes corrosion to occur and aggravate, so it is a defect that is enough to cause problems. In addition, when delivering as a polishing finish, since the time until the polishing is completed is short, it is also a necessary characteristic to have a uniform gloss from this perspective.
[0011] Furthermore, it is to be reiterated that a major problem in the conventional technology is that weldability, which becomes important when manufacturing chemical devices, is not considered.
[0012] The above patent documents are as follows:
[0013] Patent Document 1: Japanese Patent Application Publication No. 2014-1413;
[0014] Patent Document 2: Japanese Patent Application Publication No. 2013-40379;
[0015] Patent document 3: Japanese Patent Application Publication No. 10-18004;
[0016] Patent document 4: Japanese Patent Application Laid-Open No. 4-346638;
[0017] Patent document 5: Japanese Patent Application Publication No. 2018-172709. Summary of the invention
[0018] The present invention is used to solve the above-mentioned problems in the prior art, and its purpose is to provide Ni-Cr-Mo steel, which is a steel with excellent weldability that prevents cracks in welds, etc., and solves various problems caused by its hot working and has excellent surface properties.
[0019] The present invention solves the above-mentioned various problems. The Ni-Cr-Mo steel of the present invention is characterized in that, in terms of the following mass %, it contains C: 0.005-0.035%, Si: 0.02-0.25%, Mn: 0.03-0.40%, P: ≤0.030%, S: 0.0001-0.0020%, Ni: 32.0-38.0%, Cr: 21.0-25.0%, Mo: 6.0-8.0%, W: 0.01-2.0%, Cu: 2.0-5.0%, N: 0.18-0.30%, B≤0.0005%, Ca≤0.0015%, REM≤0.0020%, Al: 0.005-0.150%, Ti: 0.002-0.200%, O≤35ppm, and the balance is Fe and unavoidable impurities, and satisfies the following formulas (1) to (3):
[0020] 1.3×Mo+1.0×W﹣1.3×Cu﹣52.7×Al﹣17.9×Ti<6.5 …Formula (1)
[0021] 8.4×Si+Cu<4.70 …Formula (2)
[0022] Ti+0.625×Si<0.26…Equation (3)
[0023] In formulas (1) to (3), each element represents mass %.
[0024] A preferred embodiment of the Ni—Cr—Mo steel of the present invention contains Mg: 0.0003 to 0.0045%, and contains either or both of V: 0.005 to 0.20% and Nb: 0.005 to 0.20%.
[0025] In addition, when manufacturing the Ni-Cr-Mo steel of the present invention, it is characterized in that a raw material containing scrap steel is melted in an electric furnace, and impurity elements contained in the scrap steel are forcibly removed by blowing oxygen in an AOD process, and it is confirmed that B ≤ 0.0005%, Ca ≤ 0.0015%, and REM ≤ 0.0020% are achieved. Thereafter, when it is necessary to add raw materials for adjusting the composition, only raw materials that do not contain these elements are used as the raw materials to be added.
[0026] The Ni-Cr-Mo steel of the present invention having the above composition can prevent cracks in the weld due to the addition effects of the chemical components described below, and has excellent weldability. In addition, it solves various problems caused by hot working and has excellent surface properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a graph showing the relationship between Formula 1 of the present invention and the number of polishing times.
[0028] Figure 2 This is a graph showing the influence of the amount of Cu and the amount of Si on the ratio of the reduction of area.
[0029] Figure 3 This is a diagram showing the influence of the Ti amount and the Si amount on the number of Ti clusters. DETAILED DESCRIPTION
[0030] In view of the above situation, the inventors of the present invention have conducted in-depth research to solve the problem. First, the gloss unevenness was initially observed at two locations where differences were found visually. As a result, it was found that the surface roughness of the two was different. Here, before pickling, that is, when the appearance was confirmed in a state with oxide scale (acidified scale), although it was not obvious, the difference was found. Therefore, the part was marked, and when it was pickled in a mixed acid containing nitric acid + hydrofluoric acid in the laboratory, it was confirmed that there was the same gloss unevenness as the product. It was thus confirmed that the unevenness of the oxide scale was the cause of the gloss unevenness. In addition, since it was confirmed that the sample with a large amount of Mo addition was more serious, and if it contained a trace amount of Al, it was slightly better, so the influence of the composition was investigated in the laboratory.
[0031] In addition to the above elements, Ti, W, Cu, Mn, etc. are selected to investigate their effects. Various elements are added to 34Ni-24Cr-7Mo-0.22N as the matrix, and the amount is changed for laboratory melting (20kg), and it is forged according to 30mm×100mm×L, and the surface is ground by a forming machine to make 25mmt. After keeping it heated at 1250℃×1hr, it is immediately hot rolled using a four-roll mill. The rolling rate of the first pass is set to 20%, followed by 15% rolling, and the rolling is ended by cooling. Then, a solid solution heat treatment of 1150℃×25min is implemented, and the oxide scale is removed by pickling. At this stage, it can be confirmed that the gloss is uneven, but because the uneven occurrence area is small and scattered, it cannot be quantitatively evaluated, making it difficult to distinguish whether it is qualified. Therefore, it is cut according to 90mm×90mm, and it is ground and evaluated. The grinding device uses an automatic grinding device (MB-1 manufactured by Sankyo Rikagaku Co., Ltd.) that conveys sandpaper in a roll so that a new surface can always be used for grinding, and updates and grinds while grinding. The model of the wet sandpaper is set to #120, the surface pressure is set to 0.25 MPa, and one pass is set to 90 seconds. Once one side of the test piece is ground, the sandpaper is conveyed and ground with a new surface. The evaluation is compared with the grinding time until the surface after pickling completely disappears and becomes uniform. The plate manufactured on site and confirmed to have uneven gloss was ground in 11 passes. The convex part is ground first by grinding. The larger the concave and convex, the more obvious the uneven gloss, and the more passes are needed to make it smooth.
[0032] As a result, the following trend was observed: if the amount of Mo and W increased, the number of grinding passes to finish machining increased, and if Al and Ti were added, the number of passes decreased. Although it was observed that Cu also tended to reduce the number of passes, no obvious trend could be confirmed for other elements. Therefore, in order to quantify the influencing elements and their respective effects, a multivariate regression analysis was performed on the addition amount and its test results, and the results showed that there were various relationships in the following formula. The results are shown in Figure 1 In. According to Figure 1 The results shown show that when the value of formula (1) is set to less than 6.5, polishing can be completed within 10 passes compared to the product with uneven gloss, which is a level that can be judged to have an improved effect.
[0033] 1.3×Mo+1.0×W﹣1.3×Cu﹣52.7×Al﹣17.9×Ti<6.5 …Formula (1)
[0034] If improved to this extent, good surface properties can be formed only by pickling, and a neat and uniform appearance can be obtained compared with the past. In addition, it is known that even in the case of grinding, a uniform grinding surface can be easily obtained.
[0035] Next, in order to improve weldability, the inventors conducted the following various studies. A raw material of 34Ni-24Cr-7Mo-3.1Cu-0.22N, which is excellent in corrosion resistance, was added with a small amount of B, Ca, and REM, which are said to improve hot workability. The raw material was melted in the laboratory, and a 9mmt plate was made by hot forging. The surface was ground by a forming machine to make a 5mmt sample for the adjustable restraint test (Varestraint Test). The test conditions were set as TIG welding current value of 125A, arc length of 3mm, moving speed of 100mm / min, bending speed of 100mm / sec, bending R=100R, Ar gas flow rate of 12L / min, and the occurrence, size, and appearance of cracks after the test were compared. Since mixed rare earth (Misch metal) was used as REM, the elements contained were La, Ce, and Nd. The amounts of P and S which affect weldability were set to 0.035% and 0.0030%, respectively.
[0036] The results are shown in Table 1. The maximum crack length of the sample with added B is large. It can be seen that when B is added, which is said to improve hot workability, cracks during welding are aggravated. In addition, when Ca is added, spatter increases, and when REM is added, the weld is severely uneven, and foreign matter is confirmed. Although they are added in trace amounts, they are confirmed to have adverse effects. From this, it can be seen that these elements should be reduced from the perspective of weldability. In particular, the influence of B, which causes cracks that require time-consuming repair, should be greatly reduced and as close to zero as possible.
[0037] Table 1
[0038]
[0039] In order to ensure weldability, it is clearly preferred not to add B, Ca, and REM, but whether its hot workability is sufficient was investigated. In the state of casting only, a hot tensile test was performed using a Gleeble thermal simulation tester (manufactured by DSI) for evaluation. The test was performed at 1150°C and 950°C, and the evaluation was performed by the ratio of the respective cross-sectional reduction rates. It is an indicator used to evaluate the degree of reduction in workability by assuming the temperature reduction caused by hot working.
[0040] As shown in Table 2, the hot workability of the sample containing no B, Ca, or REM is insufficient. Therefore, although the hot workability is improved by reducing P and S, which deteriorate the hot workability, it is not at a sufficient level. It is said that P and S have an adverse effect due to their presence at the grain boundaries, and it is believed that by refining the solidified structure and increasing the grain boundary area, these elements can be relatively reduced, thereby adding Ti. Although this also has a certain effect, it still does not reach a sufficient level.
[0041] Table 2
[0042]
[0043] As mentioned above, Cu is necessary for ensuring surface quality and is also a useful element that helps ensure corrosion resistance. However, it is known to have an adverse effect on hot workability. Therefore, it was studied whether there is a way to reduce the adverse effects of Cu. It was found that reducing Si is effective. Using 34Ni-24Cr-7Mo-0.22N as the matrix, the Si amount was changed in the range of ~0.6% and the Cu amount was changed in the range of ~4%. The same method as paragraph 0026 was used to investigate how the drawing ratio changes due to the Cu and Si amounts. It was found that by reducing the Si amount, the cross-sectional reduction rate can also be ensured in the steel with Cu added (refer to Figure 2 ). It is known that if hot working is performed so that the ratio of the reduction of area without problems becomes 0.75 or more, the amounts of Si and Cu need to satisfy the following formula.
[0044] 8.4×Si+Cu<4.70 …Formula (2)
[0045] Thus, even without adding elements that are said to improve hot workability, stripe defects or cracks on the end surface can be prevented. Although it is the effect of Si and Cu, its detailed mechanism is unclear. It is known that Cu forms a liquid phase at high temperature and infiltrates at the grain boundary, thereby causing cracks. It is known that Si is also an element with a strong tendency to segregate at the grain boundary. Si intensifies the infiltration of Cu into the grain boundary, but it is speculated that this should be suppressed.
[0046] In the steel of the present invention, when the surface gloss is ensured mainly by adding Ti, nitrides are easily formed due to the high nitrogen content, and there are cases where surface defects occur due to clustering. Therefore, the relationship between the clustering of Ti nitrides and the added elements was investigated, and it was found that it was related to the Si content. Therefore, steels with different Ti and Si contents were melted in the laboratory for investigation.
[0047] The steel ingot, which was cast only and based on 34Ni-24Cr-7Mo-2.5Cu-0.22N as the matrix, was subjected to a heat treatment of 1250°C×60hr with Si and Ti varying in the range of 0.03~0.26% and 0.005~0.19%, respectively, to reduce microsegregation to some extent. The structure was observed with the observation field set to 10mm×10mm, and the number of small clusters of Ti nitrides observed therein was measured and evaluated. Samples without Ti clusters were counted as ○, samples with less than 5 Ti clusters were counted as △, samples with less than 10 Ti clusters were counted as ▲, and samples with more than 10 Ti clusters were counted as ●. The results are as follows: Figure 3As shown in the figure, the clustering of Ti nitrides is reduced by reducing the amount of Si added, and it is known that reducing the amount of Si also helps to prevent such surface defects. From the results of this experiment, it is believed that the clustering of Ti nitrides can be effectively suppressed by satisfying the following formula. In addition, the Ti nitrides also contain Ti carbonitrides in which the presence of some carbon is confirmed.
[0048] Ti+0.625×Si<0.26…Equation (3)
[0049] In the steel of the present invention, Si is an element used for deoxidation (deacidification), but Mn, Al, and Ti also have the same effect. By adding Ti, surface gloss can also be ensured, and the occurrence of clusters can also be suppressed by reducing Si. If Al is selected, there is no risk of clusters, so it is relatively the most reliable choice, but excessive addition will increase the risk of inclusions (intermediates) and reduce corrosion resistance. Deoxidation and surface gloss are both dependent on specific elements, which is not the best choice, and the proposed formula should be used to select well-balanced additive elements.
[0050] Next, the reasons for limiting the component composition, relational expressions, etc. of each element in the present invention will be described.
[0051] C: 0.005~0.035%
[0052] C is an effective element for stabilizing austenite phase, and suppresses the precipitation of σ phase which is harmful to corrosion resistance. In addition, it is also an important element for ensuring strength. Therefore, it is necessary to add at least 0.005%. However, if excessively contained, Cr carbides are easily precipitated during cooling during welding and solution heat treatment, which deteriorates corrosion resistance. Therefore, the upper limit is set to 0.035%. The preferred lower limit of content is 0.007%, and the more preferred lower limit is 0.009%, and the preferred upper limit is 0.030%, and the more preferred upper limit is 0.025%.
[0053] Si: 0.02~0.25%
[0054] Si is an important element with a deoxidizing effect, and therefore, at least 0.02% needs to be added. However, in the steel of the present invention containing Cu, if Si is excessively contained, hot workability is reduced. In addition, in the steel of the present invention in which both N and Ti coexist, cluster formation of Ti nitrides is aggravated. It is also an element that promotes the precipitation of σ phase that deteriorates corrosion resistance. Therefore, the upper limit of the Si content is set to 0.25%. The preferred lower limit of the content is 0.04%, the more preferred lower limit is 0.06%, the preferred upper limit is 0.23%, and the more preferred upper limit is 0.21%.
[0055] Mn: 0.03~0.40%
[0056] Mn is an element added as a deoxidizer. Since it has the effect of stabilizing the austenite phase and increasing the solubility of N, it suppresses the formation of carbonitrides and helps to ensure corrosion resistance. Therefore, it is necessary to contain more than 0.03% Mn. However, excessive addition will promote the precipitation of σ phase and reduce corrosion resistance. Moreover, MnS is formed, which becomes the starting point of pitting corrosion and deteriorates corrosion resistance. Therefore, the content of Mn is set to 0.03~0.40%. The preferred lower limit of the content is 0.05%, the more preferred lower limit is 0.07%, the preferred upper limit is 0.30%, and the more preferred upper limit is 0.25%.
[0057] P≤0.030%
[0058] P is an element that is inevitably mixed into steel as an impurity. It segregates at the grain boundary and deteriorates hot workability, so it needs to be reduced as much as possible. Therefore, the P content is set to ≤0.030%. The preferred range is ≤0.025%, and the more preferred range is ≤0.020%.
[0059] S: 0.0001~0.0020%
[0060] S is an impurity element inevitably mixed into steel. Since it reduces hot workability and forms sulfides, which become the starting point of pitting corrosion, it has a harmful effect on corrosion resistance. Therefore, the S content is preferably as small as possible, and the upper limit is preferably 0.0020%. However, since S improves the fluidity of the melt during melting, it is also an essential element when welding. In order to ensure weldability, it is preferably contained at least 0.0001%. The preferred lower limit of the content is 0.0002%, the more preferred lower limit is 0.0003%, the preferred upper limit is 0.0015%, and the more preferred upper limit is 0.0010%.
[0061] Ni: 32.0~38.0%
[0062] Ni is an element that stabilizes the austenite phase. It is an important element that suppresses the precipitation of intermetallic compounds such as the σ phase and improves pitting corrosion resistance and overall corrosion resistance. Therefore, it is necessary to add more than 32.0%. However, if the content of Ni exceeds 38.0%, it will lead to increased thermal deformation resistance and increased costs. Therefore, the content of Ni is set to 32.0~38.0%. The preferred lower limit of the content is 33.0%, and the more preferred lower limit is to add more than 35.0%, the preferred upper limit is 37.5%, and the more preferred upper limit is 37.0%.
[0063] Cr: 21.0~25.0%
[0064] Cr improves intergranular corrosion resistance and intergranular corrosion resistance, and is an indispensable element for the use of the steel of the present invention in the harsh environment envisioned. However, excessive Cr content promotes the precipitation of the σ phase, which in turn deteriorates the corrosion resistance. Therefore, the Cr content is set to 21.0-25.0%. The preferred lower limit of the content is 21.5%, the more preferred lower limit is 22.0%, the preferred upper limit is 24.5%, and the more preferred upper limit is 24.0%.
[0065] Mo: 6.0~8.0%
[0066] Mo improves pitting corrosion resistance and intergranular corrosion resistance in the same way as Cr, N, etc., and is an indispensable element for the use of the steel of the present invention in the harsh environment envisioned. However, if Mo is excessively contained, the precipitation of the σ phase is greatly promoted, and the corrosion resistance is deteriorated. In addition, it is known that the surface gloss is deteriorated, and excessive addition leads to quality deterioration. Therefore, the content of Mo is set in the range of 6.0~8.0%. The preferred lower limit of the content is 6.1%, the more preferred lower limit is 6.2%, the preferred upper limit is 7.9%, and the more preferred upper limit is 7.8%.
[0067] W: 0.01~2.0%
[0068] W is an element that improves pitting corrosion resistance and intergranular corrosion resistance, similarly to Mo. However, if W is excessively contained, the precipitation of the σ phase is greatly promoted, deteriorating the corrosion resistance. In addition, the surface gloss is deteriorated, similarly to Mo. Therefore, the content of W is set to a range of 0.01 to 2.0%. The preferred lower limit of the content is 0.02%, the more preferred lower limit is 0.03%, the preferred upper limit is 1.8%, and the more preferred upper limit is 1.6%.
[0069] Cu: 2.0~5.0%
[0070] Cu is an important element that stabilizes austenite phase and helps to improve sulfuric acid resistance, and is an element useful for the purpose envisioned by the steel of the present invention. In addition, it is an essential element that has the effect of preventing the surface quality deterioration caused by adding Mo and W as the characteristic of the steel of the present invention. In order to obtain this effect, it is necessary to contain more than 2.0%. However, since excessive addition can increase cost and deteriorate hot workability, the upper limit is set to 5.0%. Thus, its content is set to 2.0~5.0%. The preferred lower limit of content is 2.9%, and the more preferred lower limit is to add more than 3.0%, and the preferred upper limit is 4.7%, and the more preferred upper limit is 4.3%.
[0071] N: 0.18~0.30%
[0072] N is an element that stabilizes the austenite phase and is an effective element for suppressing the precipitation of the σ phase and improving the strength. In addition, like Cr, Mo, and W, it is an element that greatly improves the pitting corrosion resistance and intergranular corrosion resistance. Therefore, it is necessary to add at least 0.18%. However, if the N content is excessive, carbonitrides will precipitate in large quantities, reducing the corrosion resistance. In addition, if the strength is excessively increased, the processability of the manufacturing device will be reduced. Therefore, it cannot exceed 0.30%. The preferred lower limit of the content is 0.19%, the more preferred lower limit is 0.20%, the preferred upper limit is 0.27%, and the more preferred upper limit is 0.25%.
[0073] B≤0.0005%
[0074] B is an impurity element that is sometimes inevitably mixed into steel from scrap steel, etc., and is also known to improve hot workability. Therefore, if it is contained in a very small amount, there is no problem. However, if it contains more than a certain amount of B, the weldability deteriorates, cracks will occur in the weld, and the manufacturing device becomes difficult. Therefore, the upper limit is set to 0.0005%. The preferred upper limit of the content is 0.0003%, and the more preferred upper limit is 0.0002%.
[0075] Ca≤0.0015%
[0076] Ca is an impurity element that is sometimes inevitably mixed into steel from scrap steel, slag, etc., and is also known to be an element that improves hot workability. Therefore, if it is contained in a very small amount, there is no problem. However, if it contains more than a certain amount of Ca, the weldability will deteriorate, and spatter will be scattered on the weld and around it, and the manufacturability of the device will be reduced. In addition, CaO inclusions are formed, forming clusters of more than 100μm, forming surface defects in the product. Therefore, the upper limit is set to 0.0015%. The preferred upper limit of the content is 0.0013%, and the more preferred upper limit is 0.0010%.
[0077] REM≤0.0020%
[0078] REM is an impurity element that is sometimes inevitably mixed into steel from scrap steel, etc., and is also known to be an element added to improve hot workability. Therefore, if it is contained in a very small amount, there is no problem. However, if it is contained in a certain amount or more, the weldability deteriorates, foreign matter is confirmed at the weld, the appearance deteriorates, and repair is required. As a result, the manufacturability of the device is reduced. Therefore, the upper limit is set to 0.0020%. The preferred upper limit of the content is 0.0010%, and the more preferred upper limit is 0.0005%.
[0079] Al: 0.005~0.150%
[0080] Al is a component added as a deoxidizer. In addition, in the coexistence of CaO-SiO2-Al2O3-MgO slag, desulfurization is promoted by deoxidation, and S is an important element for reducing the adverse effects on hot workability. In addition, it has an important role in improving the deterioration of surface gloss caused by the addition of Mo and W together with Cu and Ti. Therefore, it is necessary to add at least 0.005%. However, if it is contained excessively, Al nitrides are formed to deteriorate corrosion resistance, thereby reducing the stability of the austenite phase. Therefore, the content of Al is set to 0.005~0.150%. The preferred lower limit of the content is 0.008%, the more preferred lower limit is 0.010%, the preferred upper limit is 0.130%, and the more preferred upper limit is 0.120%.
[0081] Ti: 0.002~0.20%
[0082] Ti is a component added as a deoxidizer. It forms Ti nitrides to refine the solidified structure, thereby reducing the P and S concentrations at the grain boundaries, and is an element that improves hot workability. In addition, it is an element that improves the surface quality reduction caused by the addition of Mo and W together with Al and Cu. Therefore, it is necessary to add at least 0.002%. However, if it is contained excessively, Ti nitrides are excessively generated, clustered, and new surface defects are generated. Therefore, the content is upper limited to 0.20%. The preferred lower limit of the content is 0.005%, the more preferred lower limit is 0.008%, the preferred upper limit is 0.18%, and the more preferred upper limit is 0.15%.
[0083] O≤35ppm
[0084] O is an impurity element that is inevitably mixed into copper during melting, and is an element that deteriorates hot workability. Therefore, elements such as Si, Ti, Al, Ca, and REM are added to the melt for deoxidation, and are elements that should be reduced. In the present invention, in order to ensure surface properties, improve hot workability, and ensure weldability, the addition amount of these elements is limited. Therefore, it is necessary to comply with the elements and their addition amounts allowed in the present invention and combine them to fully reduce the amount of oxygen. Therefore, the upper limit should be set to 35ppm. The preferred upper limit of the content is 33ppm, and the more preferred upper limit is 30ppm.
[0085] 1.3×Mo+1.0×W﹣1.3×Cu﹣52.7×Al﹣17.9×Ti<6.5
[0086] By containing Mo, W, Cu, Al, and Ti as the elements constituting the present invention within their respective specified ranges, and satisfying the relationship of the above formula, uneven surface gloss can be suppressed. In order to use in a severe corrosive environment, Mo and W must be added. In order to suppress the reduction in surface properties caused by this, Cu, Al, and Ti need to be added so that the ratio in the above formula is less than 6.5. The preferred upper limit is 6.3, and the more preferred upper limit is 6.1.
[0087] 8.4×Si+Cu<4.70
[0088] By containing Cu and Si as elements constituting the present invention within their respective specified ranges, the relationship of the above formula is satisfied, thereby ensuring hot workability. In order to use in a severe corrosive environment, Cu must be added. In order to suppress the reduction in hot workability caused by this, it is necessary to add Cu and Si so that the ratio in the above formula is less than 4.70. The preferred upper limit is 4.30, and the more preferred upper limit is 4.00.
[0089] Ti+0.625×Si<0.26
[0090] By containing Ti and Si as elements constituting the present invention within their respective specified ranges and satisfying the relationship of the above formula, the occurrence of surface defects caused by clusters of Ti nitrides can be prevented. In order to use in a severe corrosive environment, Mo and W must be added, and Ti is added to suppress the uneven surface gloss caused by this, but if Ti is added, defects of a form that has never existed before will occur. This is caused by clusters of Ti nitrides, and in order to suppress this defect, Ti and Si need to be added so that the above formula is less than 0.26. The preferred upper limit is 0.23, and the more preferred upper limit is 0.21.
[0091] Mg: 0.0003~0.0045%
[0092] Mg is an element that improves hot workability. In addition, the inclusions are controlled to be MgO that is harmless to corrosion resistance, as long as more than 40% of all inclusions are MgO. Therefore, more than 0.0003% is added as needed. However, if more than a certain amount of Mg is contained, Ca also increases and exceeds 0.0015%, weldability and corrosion resistance deteriorate, and CaO inclusions that cause clusters are formed. Therefore, the upper limit is set to 0.0045%. The preferred lower limit of the content is 0.0004%, the more preferred lower limit is 0.0005%, the preferred upper limit is 0.0040%, and the more preferred upper limit is 0.0035%.
[0093] V: 0.005~0.20, Nb: 0.005~0.20%
[0094] V and Nb are elements that form carbides or carbonitrides and refine the solidified structure. As a result, the concentration of P and S at the grain boundaries is reduced, and they are elements that improve hot workability. In addition, the structure after hot working is also refined, and they are elements that improve surface roughness. Therefore, it is necessary to add at least 0.005%. However, if it is contained excessively, carbides or carbonitrides of these elements are excessively generated, which increases the hardness and deteriorates the workability. Therefore, the content of V and Nb is upper limited to 0.20%. The preferred lower limit of the content is 0.008%, the more preferred lower limit is 0.010%, the preferred upper limit is 0.18%, and the more preferred upper limit is 0.15%. Example
[0095] Hereinafter, the present invention will be described in detail by way of examples, but the present invention is not limited to these examples unless it exceeds the gist of the present invention.
[0096] First, raw materials such as iron scraps, stainless steel scraps, and ferrochrome are melted in a 60-ton electric furnace. Then, in the AOD process, oxygen and argon are blown for decarburization and refining. Then, quicklime, fluorite, Al, and Si are added to form CaO-Al2O3-MgO slag for desulfurization and deoxidation. Then, ingots are cast using a continuous casting machine to obtain slabs with the chemical composition shown in Table 3 (Examples 1 to 29, Comparative Examples 1 to 8, size / 200mmt×1250mm×6500mm).
[0097] In terms of chemical composition values of B, Ca, and REM, samples marked as 0.0000 are below the analytical limit, indicating that oxygen blowing in AOD can reduce them to this value. Usually, the time of about 60 minutes is implemented as 85 minutes. For Mg, Nb, and Ti, samples marked as "-" indicate that they are not intentionally added.
[0098] Then, the slab is heated to 1250°C and kept for 90 minutes, and then hot rolled according to the conventional method to obtain a hot-rolled steel strip with a thickness of 8.0mm×1250mm×L. Then, a heat treatment of 1100~1150°C is carried out through a continuous annealing line, and after water cooling and pickling, its appearance is evaluated on the production line. For a coil length of 150m, the number of strip defects on the surface and back, the number of cracks on the end face, and the number of cluster defects are visually counted, and the total number is used for evaluation. For strip defects, less than 6 are counted as good, the number of cracks on the end face is counted as good, and the number of cluster defects is counted as good if it is less than 2. For inclusion species that form clusters, hot rolled strips are used for analysis using SEM-EDS.
[0099] For uneven gloss, a 90 mm × 90 mm test piece was cut from the center of the width of the sample and used for the grinding test. The grinding test was carried out in the same manner as above using an automatic grinding device (MB-1 manufactured by Sankyo Rikagaku Co., Ltd.) that can convey and update sandpaper in a roll. The test conditions were that the wet sandpaper model was #120, the surface pressure was 0.25 MPa, and one pass was 90 seconds. The number of passes until the grinding was completed was compared. The grinding was completed until the surface after pickling completely disappeared and became uniform. The case of finishing with less than 9 passes was considered good.
[0100] For weldability, test pieces were cut from the pickled strips, and both sides were formed identically to a thickness of 5 mmt for an adjustable restraint test. The test conditions were the same as above, with the TIG welding current value set to 125 A, the arc length set to 3 m, the moving speed set to 100 mm / min, the bending speed set to 100 mm / sec, the bending R=100R, and the Ar gas flow rate set to 121 L / min. The maximum adjustable restraint crack length (mm) after the comparison test was considered good for samples below 4 mm. The appearance was evaluated by observing a wide area including the weld periphery with a microscope, measuring the number of sputtering objects, and observing the weld surface to determine the number of foreign objects. The former was considered good if it was less than 30, and the latter was considered good if it was less than 10.
[0101] As shown in Table 4, Examples 1 to 29 satisfying the composition range of the present invention and the condition range of formulas (1) to (3) are found to have excellent weldability and defect-free sound surface properties.
[0102] In contrast, Comparative Examples 1, 2, and 3, in which the contents of B, Ca, and REM are outside the range of the present invention, have poor weldability and are difficult to apply to the intended uses of the steel of the present invention. In addition, since the amount of Mg in Comparative Example 2 is large, the number of Ca oxide-based inclusions increases, and surface defects caused by the clusters occur, resulting in poor surface properties.
[0103] Although Comparative Example 4 has a chemical composition that satisfies the present invention, it does not satisfy Formula (1). Therefore, uneven gloss occurs, resulting in poor surface properties. Even in the case of polishing and finishing, multiple passes are required, resulting in poor polishability.
[0104] Although Comparative Example 5 has a chemical composition that satisfies the present invention, it does not satisfy Formula (2). Therefore, the number of defects caused by hot working is large, and the surface properties are poor.
[0105] Although Comparative Example 6 has a chemical composition that satisfies the present invention, it does not satisfy Formula (3). Therefore, clusters are generated due to Ti nitrides, resulting in poor surface properties.
[0106] Since the amount of Si added in Comparative Example 7 was large, the hot workability was poor in the present invention steel containing Cu, and stripe defects and the like occurred.
[0107] The amount of Si added in Comparative Example 8 is outside the scope of the present invention, and deoxidation and desulfurization are insufficient. Therefore, hot workability is also poor. In addition, the inclusion species are mainly Ti-O-based, resulting in surface defects. Therefore, the surface properties are also poor.
[0108] Table 3
[0109]
[0110] Table 4
[0111]
Claims
1. Ni-Cr-Mo steel, characterized in that The following components are contained, in terms of mass%, C: 0.005-0.035%, Si: 0.02-0.25%, Mn: 0.03-0.40%, P: ≤0.030%, S: 0.0001-0.0020%, Ni: 32.0-38.0%, Cr: 21.0-25.0%, Mo: 6.0-8.0%, W: 0.01-2.0%, Cu: 3.0-5.0%, N: 0.18-0.30%, B≤0.0005%, Ca≤0.0015%, REM≤0.0020%, Al: 0.005-0.150%, Ti: 0.002-0.200%, O≤35ppm, and the balance is Fe and unavoidable impurities, and the following formulas (1) to (3) are satisfied: 1.3×Mo+1.0×W﹣1.3×Cu﹣52.7×Al﹣17.9×Ti<6.5…Formula (1) 3.168<8.4×Si+Cu<4.70…Equation (2) Ti+0.625×Si<0.26…Formula (3) In formulas (1) to (3), each element represents mass %.
2. The Ni-Cr-Mo steel according to claim 1, characterized in that It contains Mg: 0.0003-0.0045%, and contains either or both of V: 0.005-0.20% and Nb: 0.005-0.20%.
3. A method for producing Ni-Cr-Mo steel, characterized in that: When manufacturing the Ni-Cr-Mo steel according to claim 1, raw materials containing scrap steel are melted in an electric furnace. By blowing oxygen in the AOD process, impurity elements contained in the scrap steel are forcibly removed, and it is confirmed that B≤0.0005%, Ca≤0.0015%, and REM≤0.0020% are achieved. When it is necessary to add a raw material for adjusting the composition, only raw materials not containing these elements are used as the raw materials to be added.
4. A method for producing Ni-Cr-Mo steel, characterized in that: When manufacturing the Ni-Cr-Mo steel according to claim 2, raw materials containing scrap steel are melted in an electric furnace. By blowing oxygen in the AOD process, impurity elements contained in the scrap steel are forcibly removed, and it is confirmed that B≤0.0005%, Ca≤0.0015%, and REM≤0.0020% are achieved. When it is necessary to add a raw material for adjusting the composition, only raw materials not containing these elements are used as the raw materials to be added.
Citation Information
Patent Citations
Sulfuric acid dew point corrosion resistant stainless steel excellent in hot workability
JP1992346638A
Austenitic stainless steel excellent in sulfuric acid corrosion resistance
JP1998018004A
Corrosion resistant alloy excellent in workability
JP2013040379A
Ni-BASED ALLOY
JP2014001413A
Austenitic stainless steel, soldered structure, soldered structure component and exhaust gas heat exchange component
JP2018172709A